2020
DOI: 10.1080/22221751.2020.1818631
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Ephrin receptor and PPAR signaling pathways in neural progenitor cells infected by Zika virus

Abstract: Zika virus (ZIKV) infection is a serious public threat with cases reported in about 70 countries and territories. One of the most serious consequences of ZIKV infection is congenital microcephaly in babies. Congenital microcephaly has been suggested to result from infection of neural progenitor cells (NPCs) in the developing fetal brain. However, the molecular and cellular mechanisms underlying microcephaly development remains to be fully elucidated. In this study, we employed quantitative proteomics to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
(85 reference statements)
0
14
0
Order By: Relevance
“…Influenza virus strain was studied in MDCK cells in serum‐free MEM, containing 1 μg/ml trypsin TPCK‐treated (Sciex), 2 mM L‐glutamine, 100 U/ml penicillin, and 0.1 mg/ml streptomycin. Evaluation of virus titers and viral growth curves were carried, according to standard protocols 44 . In the present study, we have probed different concentrations of p‐cymene (up to 2 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza virus strain was studied in MDCK cells in serum‐free MEM, containing 1 μg/ml trypsin TPCK‐treated (Sciex), 2 mM L‐glutamine, 100 U/ml penicillin, and 0.1 mg/ml streptomycin. Evaluation of virus titers and viral growth curves were carried, according to standard protocols 44 . In the present study, we have probed different concentrations of p‐cymene (up to 2 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of virus titers and viral growth curves were carried, according to standard protocols. 44 In the present study, we have probed different concentrations of p-cymene (up to 2 mg/ml).…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…PPARα activation contributes to rapid repair of intestinal epithelium during SIV infection in macaque models ( 54 ). Interestingly, certain viral infections, such as Zika virus, have been shown to modulate and dysregulate PPARα signaling pathways in human cells ( 88 ). The core protein of hepatitis C virus (HCV) was also found to inhibit PPARα expression in humans ( 89 ).…”
Section: Viruses and Pparsmentioning
confidence: 99%
“…Notably, PPARγ transcript levels were found to be increased in human NPCs derived from induced pluripotent stem cells (iPSC), as revealed by RNA-seq, along with productive infection, proliferation arrest and apoptosis ( [99], and supplemental data therein). A more recent study used quantitative proteomics and transcriptomics in ZIKV-infected human NPCs and revealed, however, decreased levels of PPARγ mRNA [100]. The same study reported upregulation of RXRγ, of a positive regulator of PPARγ activity (Signal transducer and activator of transcription [STAT] 5 [101]) and of two negative regulators of PPARγ activity (FGR, a member of the Src family of tyrosine protein kinases [102], and the AP-1 transcription factor c-Jun [103]), whereas nuclear receptor coactivator 1 (NCOA1), a coactivator of both RXR and PPARγ [104], was found to be downregulated.…”
Section: Pparγ the Developing Brain And Zika Virusmentioning
confidence: 99%